Livestock production prospects for tropical Africa in the year 2000 - International Livestock Centre for Africa (1980)
Discusses the general prospects for demand and supply of meat and dairy products in tropical Africa, w. emphasis on factors influencing supply & demand such as population growth, rising incomes, and traditional production blockages. Analyses supply prospects from existing livestock production systems, and points out some development paths to be followed such as trypanosomiasis eradication and improvement of tradition production and smallholder fattening systems.